Innovation as a Key Success for Competitive Excellence Strategy in SMEs of Iraq - Almrshed, Sattar Kadim Hachim; Alaboody, Ali Abd Al Razaq; Jundi, Muslim Jabbar (South Asian Journal of Social Sciences and Humanities, 2024)
The paper tests the influence of innovation on competitive excellence strategy in detergent  and soap SMEs in Iraq. The study is a cross-sectional. The researchers used a random  sampling to collect the data. The sample size was of 390. Finding show that the influence of  innovation on the “competitive” excellence strategy is positive and significant, the results  show that SMEs would finance in innovative activities to improvement competitive  advantage. Further, the study proposes that this framework should investigate the effect of  innovation on competitive excellence strategy in other cont6ext of Iraqi SMEs. The limitation  and future recommendation are discussed in the end.
Keywords: Innovation,; competitive excellence strategy; SMEs